Effect of Extraction Methods on Physicochemical and Functional Properties of Nannochloropsis Proteins - Suyan HUANG; Rong CAO; Nan LIU; Yong SUN; Deqing ZHOU; Shanshan WANG (Shipin gongye ke-ji)
Nannochloropsis freeze-thawed extraction protein (NFP), Nannochloropsis enzyme-assisted extraction protein (NEP) and Nannochloropsis alkali extraction protein (NAP) were extracted from the Nannochloropsis powder by using freeze-thawed salt precipitation method, enzyme-assisted extraction method and alkali dissolution acid precipitation method, respectively. The physicochemical properties and functional properties were compared and analyzed. The results showed that the extraction rate of alkali-solution and acid-precipitation was 18.70%±0.50%, which was significantly higher than that of the other two extraction methods (P<0.05). NFP, NEP and NAP all contained a variety of essential amino acids, accounting for 38.75%, 38.16% and 37.88% of the total amino acid content, respectively. The UV absorption spectrum showed that the three extracted proteins exhibited strong absorbance values at 200~220 nm. Fourier transform infrared spectroscopy (FTIR) showed that all three proteins displayed typical protein absorption peaks, however, the secondary structure changed. After alkaline extraction treatment, the proportions of β-turn in NAP decreased to 19.62%±1.48%, respectively, whereas the β-sheet content increased to 32.90%±1.55%. Compared with NEP and NFP, the free sulfhydryl content and Zeta potential absolute value of NAP were significantly increased, while the particle size was obviously reduced (P<0.05). The results of scanning electron microscopy (SEM) showed that the microstructure of the three proteins was different. Functional properties analysis demonstrated that the solubility, foaming ability and foaming stability of the three proteins displayed similar trends with that of pH. Compared to NEP and NAP, NFP had better functional capacities. The results provide a certain theoretical basis for the development and utilization of Nannochloropsis protein resources in the food industry.